KONSEP PENDIDIKAN MULTIKULTURALISME PERSPEKTIF MAQASHID SYARI’AH UNTUK PENGUATAN PROFIL PELAJAR PANCASILA - Munir, Asep; Munir, Asep Arsyrul (INTEGRATIF |Jurnal Magister Pendidikan Agama Islam, 2024)
Religious multiculturalism awareness is needed in society in order to realize interfaith harmony. However, the formation of such awareness faces challenges in the form of conflicts of values and beliefs between groups. The purpose of this research is to identify solutions to value conflicts within the framework of forming awareness of religious multiculturalism from the maqashid shari'ah perspective. The research method used in this analytical paper is a bibliometric study that refers to the principles developed in the two disciplines of Maqashid Shariah and Multicultural Education. The results of the analysis show that the reconstruction of an inclusive religious education curriculum is a strategic solution, by incorporating the values of tolerance, justice and equality as the foundation of multicultural education. In conclusion, the formation of multicultural-religious awareness through an inclusive curriculum can minimize value conflicts. This requires the cooperation of relevant stakeholders in its implementation. Further research is recommended to evaluate the effectiveness of the inclusive curriculum implementation in fostering moderate tolerance from the maqashid shari'ah perspective.